Challenges to Athletes during the Home Confinement Caused by the COVID-19 Pandemic - Andreato L.V.* (2020)
Copyright © National Strength and Conditioning Association.The world is currently facing a serious coronavirus pandemic (COVID-19). This novel coronavirus is a new virus for which effective drugs and vaccines have not yet been developed. Amateur and professional athletic events around the world have been stopped, and teams and athletes have had to adopt social withdrawal measures, interrupting their training and preparation routines for competitions. Given this alarming scenario, this article aims to alert athletes to the importance of maintaining a conditioning routine during this confinement period.